2008
DOI: 10.1021/tx800179f
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Titanium Dioxide Nanoparticles in Mouse Fibroblast Cells

Abstract: Nanotitanium dioxide (TiO2) is an important industrial material that is widely used as an additive in cosmetics, pharmaceuticals, and food colorants. Although the small size of the TiO2 nanoparticle is useful in various applications, the biosafety of this material needs to be evaluated. In this study, mouse fibroblast (L929) cells were used to evaluate the cytotoxicity of different concentrations (3-600 microg/mL) of homogeneous and weakly aggregated TiO2 nanoparticles in aqueous solution. The L929 cells becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
201
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(230 citation statements)
references
References 36 publications
28
201
0
1
Order By: Relevance
“…The direct contact assay is the most sensitive for testing the cytotoxicity of the medical devices; the medical devices can be measured even with weak cytotoxicity (18). The agar overlay assay is suitable for the medical devices that have large toxicity and bulk filtering (19) and the molecular filtration method is suitable for the biocompatibility evaluation of the toxic components of small molecular weight medical devices (20). Gao et al (21) identified a good correlation between the direct and indirect contact test and a lesser association between the extract test and the other two trials.…”
Section: Introductionmentioning
confidence: 99%
“…The direct contact assay is the most sensitive for testing the cytotoxicity of the medical devices; the medical devices can be measured even with weak cytotoxicity (18). The agar overlay assay is suitable for the medical devices that have large toxicity and bulk filtering (19) and the molecular filtration method is suitable for the biocompatibility evaluation of the toxic components of small molecular weight medical devices (20). Gao et al (21) identified a good correlation between the direct and indirect contact test and a lesser association between the extract test and the other two trials.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of TiO 2 NPs has been discussed (Jin et al, 2008). It has been reported that TiO 2 NPs can cause respiratory toxicity and disturbances in metabolism (Federici et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the cytotoxicity of dental alginates was assessed through cytotoxic tests performed with mouse fibroblast L929 cells, a method largely used in several works evaluating the cytotoxicity of materials for use in dentistry (Alcaide et al, 2008;Donadio et al, 2008;Feizzadeh et al, 2008;Jin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%